INFLUENCE OF COMPOSITION AND THERMAL HISTORY OF VOLCANIC GLASSES ON WATER CONTENT AS DETERMINED BY MICRO-RAMAN SPECTROMETRY - Muro A.D.; Villemant B.; Giordano D.; Romano C.; Montagnac G.; Scaillet B. (My University, 2006)
Development of Raman spectrometry for quantification of water content in natural glasses requires the assessment of the dependence of the technique on glass composition and thermal history. In the low frequency domain, Raman spectra topology varies due to glass depolymerization and substitution in the framework of (Si4+)IV by alkali-balanced (Al3+)IV and (Fe3+)IV in calcalkaline (rhyolite to basaltic andesite) and alkaline (trachyte, phonolite to alkali basalt) glasses. These processes result in strong dependence of previous analytical procedure (internal calibration) on glass composition. Here, we show that an analytical procedure based on calibration to an external standard is only faintly composition-dependent for Si-rich alkaline glasses (trachytes-phonolites). For a given glass composition, thermal history also plays a fundamental role in the choice of Raman procedure for water analysis. Repeated cycles of thermal annealing induce microcrystallization of hydrous trachyte glasses and modify cation distribution in the glass structure. Application of these concepts to analysis of banded obsidians suggests that small-scale heterogeneities in glasses are not simply related to magma degassing, but could depend on thermal history and consequent relaxation paths in the melt. © 2006 Elsevier Ltd. All rights reserved.
Keywords: ALKALINE MAGMAS; GLASSES; OBSIDIAN; RAMAN; VISCOUS DISSIPATION; VOLATILES; WATER